Dabigatran for treatment and secondary prevention of venous thromboembolism in pediatric congenital heart disease - Albisetti Pedroni, Manuela; Tartakovsky, Igor; Halton, Jacqueline; Bomgaars, Lisa; Chalmers, Elizabeth; Mitchell, Lesley G.; Luciani, Matteo; Nurmeev, Ildar; Gorbatikov, Kirill; Miede, Corinna; Brückmann, Martina; Brandão, Leonardo R. (Journal of the American Heart Association, 2024)
Background - Congenital heart disease (CHD) is common in children and associated with greater risk of thrombotic complications. Management of these complications with standard‐of‐care treatment is suboptimal for these children. - Methods and Results - The effectiveness and safety of dabigatran were demonstrated in pivotal pediatric studies for the treatment of acute venous thromboembolism (VTE; NCT01895777) and secondary VTE prevention (NCT02197416). We report safety and efficacy outcomes from subgroup analyses of these studies for children with CHD (diagnosed according to local practice) and those without. In NCT01895777, 17/21 (81.0%) and 16/27 (59.3%) patients with CHD (including cyanotic) treated with dabigatran and standard of care, respectively, met the primary end point (complete thrombus resolution, freedom from recurrent VTE, and freedom from VTE‐related death; odds ratio [OR], 0.34 [95% CI, 0.08-1.23]). In patients without CHD, 41.0% (n=64) versus 34.9% (n=22) achieved this end point with the respective treatments (OR, 0.77 [95% CI, 0.42-1.41]). Although numerical differences were observed, no heterogeneity in treatment effect of dabigatran on the composite primary end point was detected in patients with and without CHD (interaction P =0.2674). In NCT02197416, recurrent VTE at 12 months occurred in 0/17 patients with CHD versus 3/194 (1.5%) without. No patient with CHD experienced major or clinically relevant nonmajor bleeding events. - Conclusions - Data on favorable anticoagulant alternatives for the unmet needs of children with CHD are emerging, and our exploratory results suggest that dabigatran could be an appropriate treatment choice, although challenging sample size limitations in pediatric studies require cautious interpretation of findings. - Registration - URL: https://www.clinicaltrials.gov; Unique identifiers: NCT01895777, NCT02197416.
Zuerst veröffentlicht: 13. Februar 2024
Gesehen am 25.02.2025